δ-primary subhypermodules on Krasnerhyperrings - Kaya, Elif; Bolat, Melis; Ersoy, Bayram Ali; Onar, Serkan; Hila, Kostaq; Davvaz, Bijan (SHAHID BEHESHTI UNIV, FAC MATHEMATICAL SCIENCES, 2024)
In this paper, we study commutative Krasner hyperrings with nonzero identity and nonzero unital hypermodules. We introduce a new con- cept, the 5-primary subhypermodule on Krasner hyperrings. Some character- izations and properties for delta-primary subhypermodules using the expansion function & are provided. The images and inverse images of delta-primary sub- hypermodules under homomorphism are investigated. Finally, some charac terizations for multiplication hypermodules with some special conditions are provided.
Keywords: delta-primary subhypermodules; expansion of subhypermodules; multiplication hypermodules; Krasner hyperrings; IDEALS; Mathematics